Misja ewangelisty w protestantyzmie anglosaskim - Krauze, Łukasz (Annales Missiologici Posnanienses, 2019)
The service of an evangelist is an important element of anglosasc protestantism. An evangelist has a huge influence on believers in shaping the awareness of their experience of God. He can do it by his zeal in calling for conversion and reminding about the meaning of the cross. Thanks to a style of his preaching he provides an audience to emotions that are necessary in a progress of the faith. The office of an evangelist was forgotten in a reality of the Catholic Church, although it has biblical roots. For this reason, it is to worth to pay attention to the mission of the evangelist in a catholic context.